55.0k views
2 votes
Find the solution of 64 = 16u algebraically.

User RedVelvet
by
4.9k points

2 Answers

4 votes

Answer:

u=4

Explanation:

User Elisabetta
by
4.7k points
4 votes

Answer:

Simplifying

64 = 16u

Solving

64 = 16u

Solving for variable 'u'.

Move all terms containing u to the left, all other terms to the right.

Add '-16u' to each side of the equation.

64 + -16u = 16u + -16u

Combine like terms: 16u + -16u = 0

64 + -16u = 0

Add '-64' to each side of the equation.

64 + -64 + -16u = 0 + -64

Combine like terms: 64 + -64 = 0

0 + -16u = 0 + -64

-16u = 0 + -64

Combine like terms: 0 + -64 = -64

-16u = -64

Divide each side by '-16'.

u = 4

Simplifying

u = 4